1630. What is Treatment Time Zero Among Hospitalized Patients with Bacteremia?. (31st December 2020) - Caffrey, Aisling; Lopes, Vrishali
Abstract: Background: Common operational definitions of antibiotic exposures in infectious diseases research do not accurately reflect actual treatment, as daily changes in clinical presentation (i.e. improvement, worsening) and clinical information (i.e. causative organism, susceptibilities) lead to frequent changes in treatment, both within empiric and definitive treatment periods. Common definitions create periods of 'ignored' exposures, and we've previously shown that antibiotic treatments during 'ignored' periods vary widely. Therefore, we assessed the distribution of important time points for antibiotic treatments for Staphylococcus aureus bacteremia. Methods: Our retrospective cohort study included hospital admissions in the national Veterans Affairs (VA) Healthcare System with S. aureus positive blood cultures from 2010 to 2018. Admissions with inappropriate initial antibiotic therapy for S. aureus were excluded. We implemented daily exposure mapping to identify antibiotic exposures and changes in treatment on each day of the admission until discharge, or 30 days post-admission for longer stays, and in relation to the culture final report date. Results: We identified 21, 947 admissions meeting our inclusion criteria. Antibiotic initiation most often occurred on the culture collection date (68.7%) or the day after (22.6%). Median time to the culture final report date from the culture collection date was 4 days (interquartile range [IQR] 3 to 5). Among those with changes in therapy (n=19, 392, 88.4%), median time to first change in therapy was 2 days prior to the culture final report date (IQR -3 to -1). The first change in therapy occurred before the culture final report date for 76.3% of admissions and on the culture final report date for 11.9% of admissions. Further changes were common on the culture final report date (49.5%) and the day after the final report date (45.3%). Conclusion: Changes in antibiotic therapy are common prior to finalization of culture reports. While initial culture results and provider knowledge of these initial results are not date/time-stamped, initial change within a reasonable period from culture collection appears to be more accurate in defining empiric and definitive treatment periods than commonly used operational definitions. Disclosures: Aisling Caffrey, PhD, Merck (Research Grant or Support)Pfizer (Research Grant or Support)Shionogi (Research Grant or Support)